Cross-cultural adaptation and validation of cognitive emotion regulation questionnaire: a systematic review - Fekar Gharamaleki, Fatemeh; Fathipour-Azar, Zeinab (Frontiers in Psychology, 2025)
BackgroundThe Cognitive Emotion Regulation Questionnaire (CERQ) is an important instrument for assessing the perceived effectiveness of emotional regulation strategies. It has been adapted into numerous regional languages worldwide. This systematic review seeks to explore the various versions of the CERQ, focusing on their processes of linguistic and cultural adaptation, as well as their validity and reliability.MethodsArticles were systematically extracted from the literature review using search engines such as PubMed, Google Scholar, Web of Science, and Scopus. The focus was on identifying studies published in English between the years 2000 and 2024. This review also encompassed various versions of the CERQ that had been adapted and validated to accommodate linguistic and cultural differences.ResultsThe original database yielded 1,476 search results. After filtering out duplicates, 420 articles were examined. Following a review of the titles and abstracts, 21 studies were identified for further evaluation. Ultimately, 13 versions were chosen for the final analysis.ConclusionThis review offers an in-depth insight into the difficulties faced in cross-cultural adaptation and the psychometric assessment processes. Notably, the predominant approach for translation identified in the reviewed literature was Brislin’s classic back-translation model. The findings demonstrate strong test–retest reliability, excellent internal consistency, and reasonable construct validity across various languages, affirming the usability of the translated versions of the CERQ in different linguistic contexts.